AGING ACROSS THE STATES. (11th November 2018) - Rehkopf, D; Furstenberg, F; Rowe, J
Abstract: Late life age-specific mortality rates vary considerably across individual States in the U.S. In addition, States are acquiring additional flexibility regarding the establishment of policies and programs that are directly relevant to the status of older persons. Despite substantial information regarding the policy and program context and general economic conditions in individual States, little is known regarding the relationship between such contextual factors and the actual status (Successful Aging) of older persons. Using data from the CDCs Behavioral Risk Factors Surveillance Survey (BRFSS) (2001–2015) with individual level data developed a rank order of the States with respect to several measures of well being of older persons (mental health, physical health, general health and mortality). States are ranked for the year 2001 and for the change over time for each measure of well being from 2001 to 2015. This analysis was followed by an evaluation of the relationship between the absolute well being of older persons and State-specific contextual factors including aging-relevant policies, supports and services and general characteristics such as economic status. This latter analysis is based on several data sources including the 2017 Senior Report of America's Health Rankings from HHS. In addition, in a sub-analysis of the impact of the great recession, there was a substantial variability across states in the changes in health status of the elderly during the recession These changes were not related to the economic impact on States as reflected in the Hacker Economic-Security Index.